(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Fallopian tube abnormalities are a common cause of female infertility. In resource-limited settings like Bangladesh, Hysterosalpingography (HSG) is the preferred initial screening tool, though Laparoscopy remains the definitive "gold standard." This study was to determine the diagnostic accuracy of HSG in detecting tubal occlusion and peritoneal factors compared to Laparoscopy. Methods: This cross-sectional study was conducted on 49 infertile women (aged 18–38 years) who were admitted to Sir Salimullah Medical College Mitford Hospital, Dhaka for laparoscopy and who had their previous HSG report available. Patients with active pelvic inflammatory disease (PID) or a history of pelvic tuberculosis or tubal surgery between the HSG and laparoscopy were excluded. HSG findings were validated against laparoscopic chromopertubation. Results: HSG showed high sensitivity (91.7%) but inappreciably poor specificity (23.1%) for tubal factors. Laparoscopy identified peritubal adhesions and tubo-ovarian distortions in over 40% of cases that were undetectable by HSG. Conclusion: HSG is an effective screening tool; however its high false-positive rate necessitates laparoscopic confirmation for definitive diagnosis and therapeutic planning. Ibrahim Cad Med J 2025, 15(1): 33-36